HUBUNGAN PERILAKU CUCI TANGAN PAKAI SABUN DENGAN KEJADIAN DIARE DI SD ADVENT SARIO KOTA MANADO - Djarkoni, Ilham Habib; Lampus, Benedictus S.; Siagian, Iyone E.T.; Kaunang, Wulan P.J.; Palandeng, Henry M.F. (UNIVERSITAS SAM RATULANGI, 2014)
Background: Diarrhea is a condition as the passage of three or more loose or liquid stools per day or more frequent passagethan is normal for individual . Research Objective: To analyze the relationship between hand-washing behavior toward theincidence of diarrhea in Manado Advent Sario Elementary School. Methods: This research using cross sectional survey approach.The population in this study were all children who are presence and attending the class and still active as the sixthgrade students. Sampling was done using purpossive random sampling, as many as 31 children were taken as samples.Results: The study shows the number of children who have a good handwashing with soap behavior is 31 children (90.3%),and those who have less behavior is 4 children (9.7%). Elementary school students who have a diarrhea occurence in thelast 6 month is 9 children (29%), while children who do not have any diarrhea incident is 22 children (71%). Conclusion:There is a relationship between the behavior of handwashing with soap toward the occurrence of diarrhea in children ofprimary school age in Manado Advent Sario Elementary School with p = 0.03, this means there is a significant relationshipbetween handwashing with soap and the occurrence of diarrhea.Keywords: washing hands with soap, diarrhea incidence, school children